PERBANDINGAN HASIL PERHITUNGAN PREMI ASURANSI JIWA ENDOWMENT SUKU BUNGA VASICEK DENGAN DAN TANPA SIMULASI MONTE CARLO - SARI, DESI KURNIA; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika, 2017)
Vasicek is one of the stochastic interest rate model that can capture interest rates movement. The aim of this research was to get the comparison of the level premium for an endowment life insurance under stochastic interest rate without and by using Monte Carlo simulation. The result show that the level premium without Monte Carlo simulation is not much different from the result of the level premium by using Monte Carlo simulation. However, the premium calculation  by using Monte Carlo simulation can also be searched the range of losses and gains of the insurance company at certain confidence interval. In this case using a confidence interval of 95%.
Keywords: Premium calculation; Endowment life insurance; Vasicek; Monte Carlo simulation